Mitigation Strategies for Human–Tibetan Brown Bear (Ursus arctos pruinosus) Conflicts in the Hinterland of the Qinghai-Tibetan Plateau - Yunchuan Dai; Yi Li; Yadong Xue; Charlotte E. Hacker; Chunyan Li; Babar Zahoor; Yang Liu; Diqiang Li; Dayong Li (Animals, 2022)
Personal injury and property damage caused by wildlife can worsen the relationship between humans and wildlife. In recent years, conflicts between herders and Tibetan brown bears (Ursus arctos pruinosus) (human–bear conflicts; HBCs) on the Qinghai-Tibetan Plateau have increased dramatically, severely affecting community motivation for the conservation of brown bears and other species. Understanding the types, effectiveness, and flaws of current HBC mitigation measures is critical to develop effective strategies to alleviate HBC. From 2017 to 2019, we conducted a systematic field survey regarding HBCs on the Qinghai-Tibetan Plateau. In addition, we invited bear specialists and multiple interest groups to hold an HBC seminar and proposed some potential mitigation strategies. We surveyed 312 families via semi-structured interviews and documented 16 types of HBC mitigation measures. A total of 96% of respondents were using more than two mitigation measures simultaneously. The effectiveness evaluation of HBC mitigation measures showed that: (1) removing food from winter homes while herders were at their summer pastures and asking people to keep watch of winter homes were effective at protecting food and houses; (2) traditional grazing methods (human guarding of livestock all day) and solar soundboxes (attached to livestock) were effective at protecting free-range livestock; (3) solar street lights had a deterrent effect on brown bears and were effective in protecting livestock, houses, and people; and (4) due to the unstable power supply of photovoltaic cells and improper installation of ground wires, electric fences were not ideal in practice. Evaluation of the potential mitigation measures at the seminar showed that upgrading electric fence technology, expanding electric fence pilot areas, installing diversionary feeders, and introducing bear spray were the most optimal solutions. This study provides a scientific basis for creating human–bear coexistence plans on the Qinghai-Tibet Plateau.